A2_1 How to train your Kraken - Davies, C. T.; Garratley, R.; Cheshire, K. J.; Moore, J. (Physics Special Topics, 2016)
We investigate wave propagation through water and its frequency dependance to determine the maximum distance Davy Jones’ Kraken can be from the Flying Dutchman and still hear his summoning call. We found the range to be 3.2 ± 0.7 km, which is much less than expected as the Flying Dutchman is unlikely to be able to produce sounds loud enough for a greater range.